2021
DOI: 10.3892/etm.2021.10028
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculatory disturbance in acute liver injury

Abstract: Microcirculatory disturbance is thought to be involved in the pathogenesis of acute liver injury (ALI). The current study examined the pathophysiologic role of hepatic microcirculatory disturbance in patients with ALI and in mouse models of ALI. Using serum aminotransferase (ALT)/lactate dehydrogenase (LDH) ratio as a hypoxic marker, 279 patients with ALI were classified into the low ALT/LDH ratio (ALT/LDH ≤1.5) and high ALT/LDH ratio group (ALT/LDH >1.5). In the low ALT/LDH ratio group, serum ALT, LDH, fibrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…We strati ed patients with ALF into high-LDH and low-LDH subgroups based on their serum ALT/LDH ratio. The high-LDH subgroup had serum ferritin elevation, microcirculatory disturbance, and subsequent intrahepatic hypoxia [20]. In this study, we analyzed the effectiveness of TASIT for ALF in high-and low-LDH subgroups and found that TASIT improved the prognosis and increased PT% in ALF in the high-LDH, but not in the low-LDH, subgroup.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…We strati ed patients with ALF into high-LDH and low-LDH subgroups based on their serum ALT/LDH ratio. The high-LDH subgroup had serum ferritin elevation, microcirculatory disturbance, and subsequent intrahepatic hypoxia [20]. In this study, we analyzed the effectiveness of TASIT for ALF in high-and low-LDH subgroups and found that TASIT improved the prognosis and increased PT% in ALF in the high-LDH, but not in the low-LDH, subgroup.…”
Section: Discussionmentioning
confidence: 92%
“…The normal ranges of ALT and LDH in this facility were 6-30 and 119-229 U/L, respectively. To focus on the degree of elevation, we set up an index calculated by the following formula: ALT/LDH ratio = (serum ALT−ULN)/(serum LDH−ULN) (ULN: upper limit of normal) as described previously [20].…”
Section: Alt/ldh Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…The high-LDH subgroup had serum ferritin elevation, microcirculatory disturbance, and subsequent intrahepatic hypoxia. [20] In this study, we analyzed the effectiveness of TASIT for ALF in high- and low-LDH subgroups and found that TASIT improved the prognosis and increased PT% in ALF in the high-LDH, but not in the low-LDH, subgroup. Serum ferritin concentrations increase in acute hepatitis, and the source of ferritin is thought to be damaged hepatocytes.…”
Section: Discussionmentioning
confidence: 99%